PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA KOPERASI PATRA SRIWIJAYA PALEMBANG - Maswah .; Agustina Marzuki; Resti Ratna Sari (JURNAL KOMPETITIF, 2018)
This research basically aims to examine the Effect of Organizational Culture and Organizational Commitment towards Employee Performance at Palembang Patra Sriwijaya Cooperative. The researcher tried to find out how the influence of organizational culture and organizational commitment both in simultaneously and partially on employee performance at the Patra Sriwijaya Cooperative in Palembang. The sample in this study were 35 employees of Palembang Patri Sriwijaya Cooperative, based on the results of answers to questionnaires distributed to employees of the Palembang Sriwijaya Patra Cooperative and then analyzing the data obtained using quantitative data analysis which included validity and reliability tests, tests classical assumptions, multiple regression analysis, hypothetical testing (F test and t test), and analysis of the correlation coefficient (r) and determination coefficient (R2). The results showed the multiple linear regression equation as follows: Y = 5.593 + 0.338 X1 + 0.435 X2 + e, with a determination coefficient of 0.950 or 95% which means that variations in Performance can be explained by Organizational Culture and Organizational Commitment. While the rest of 0.05 (5%) is explained by other factors not examined in this study. Keywords: Organizational Culture, Organizational Commitment, and Performance